Anthelmintic efficiency of medicinal forms of albendazole received on mechanochemical technologies and use of address delivery Drug Delivery System on laboratory model - I. I. Glamazdin; I. A. Arkhipov; I. M. Odoevskaja; N. V. Hiljuta; S. S. Halikov; J. S. Chistjachenko; A. V. Dushkin (Российский паразитологический журнал)
The efficiency of various forms of albendazole prepared on mechanochemical technologies with use of address delivery DDS (Drug Delivery System) is tested on white mice experimentally infected with Trichinella spiralis in a doze of 250 larvae and Hymenolepis nana in a doze of 200 eggs. The form № 2 in a doze of 10 mg/kg has shown 100% efficiency against T. spiralis and H. nana. Albendazole in the same doze has shown respectively 73,1 and 10,1% effect.